A new variety of Solanum americanum Mill. (Solanaceae), from Eastern Ghats, India - Murugan, P.; Kalidass, C.; Panda, P. C. (Bangladesh Journal of Plant Taxonomy, 2016)
Not available. Bangladesh J. Plant Taxon. 23(1): 83-85, 2016 (June)